Evaluation of nutritional status of HIV infected females during menstrual cycle in Nnewi, Anambra state, Nigeria - R. Ukibe, N.; C. Onyenekwe, C.; E. Ahaneku, J.; N. Ukibe, S.; C. Meludu, S.; F. Emelumadu, O.; O. Ifeadike, C.; L. Ilika, A.; O. Ifeanyichukwu, M.; O. Igwegbe, A. (Scientific Journal of Medical Science, 2013)
Background and Objectives: The present study was designed to evaluate the nutritional status of HIV infected females during menstrual cycle in Nnewi, Anambra State Nigeria. Materials and Methods: A total of 87 premenopausal females with regular menstrual cycle (27-31 days) and aged 15 - 45 years were randomly recruited for the study. 27 apparently healthy female participants were recruited and served as Control group while the remaining 60 participants were HIV infected females and were grouped according to WHO criteria for HIV staging into (i) Asymptomatic HIV infected females (n=20), (ii) Symptomatic HIV infected females (n=20), (iii) Symptomatic HIV infected females on ART (n=20). Blood samples were collected at follicular and luteal phases of menstrual cycle for determination of Zinc, Copper, Total protein, Albumin, iron and Haemoglobin. Results: The result showed that the levels of Zn, Cu, Total protein, Albumin, Haemoglobin were significantly lower in Asymptomatic HIV infected females, Symptomatic HIV infected females and Symptomatic HIV infected females on ART compared to Control at follicular and luteal phases of menstrual cycle (P<0.05). Zn, Cu, Total protein, Albumin, Fe and Hb were significantly higher in Symptomatic HIV infected females on ART compared to Asymptomatic and Symptomatic HIV infected females at follicular and luteal phases of menstrual cycle (P<0.05). Conclusion: The result showed significant nutritional deficiency in HIV infected females at follicular and luteal phases of menstrual cycle which was improved in the participants who were placed on ART.